2017
DOI: 10.5935/2525-5711.20170036
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of oral precancer and cancer in south kerala population

Abstract: Introduction: Oral cancer is a major concern in developing countries. India accounts for one third of worlds oral cancer and has a high rate of oral precancer. Early detection of premalignant conditions can improve the prognosis of the disease. Objective: 1.To evaluate the prevalence of oral precancer and oral cancer among patients in south Kerala, India. 2. To evaluate the association of tobacco related oral precancer and oral cancer with abusive habits. Methods: A total number of 10999 patients, aged 20-80yr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 12 publications
2
12
2
Order By: Relevance
“…It is usually observed in the general population in different age groups and both genders. 17 The present study demonstrated the absence of fissures in 205 (65.7 %) of participants.…”
Section: Discussionsupporting
confidence: 51%
“…It is usually observed in the general population in different age groups and both genders. 17 The present study demonstrated the absence of fissures in 205 (65.7 %) of participants.…”
Section: Discussionsupporting
confidence: 51%
“…In the present study, the prevalence of lichen planus was obtained as 49.2%, while this number was 30.8% in the Chher study(28). On the other hand, in Mathew's study, as in the current study of Lichen Plan, OPML was the most common lesion in the population (23).…”
Section: Discussioncontrasting
confidence: 39%
“…In the present study, there was no signi cant difference in the gender of OPML patients. But in other studies, OPML has a signi cant difference in male gender compared to female (21,23,28).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Leukoplakia was identified as the most common PMD by Hosagadde et al 11 , in Mumbai (45.71%) and Aroquiadasse et al 15 , in Pondicherry (38.4%). There are contradictory results from other studies where OSMF 2,12,17,23 and Lichen planus were found to be most prevalent PMD 24 . This alteration could be due to the differences in chronicity, composition, method of smoking/ chewing and combinations of habits which is prevalent in respective areas.…”
Section: Discussionmentioning
confidence: 74%